Medicine is the profession of their destiny - Bokarius, Leonid; Boсarius Serhii; Filipenko, Nataliia (Archives of Criminology and Forensic Sciences, 2020)
The complex process of deThe phrase “labor dynasty” has a deep meaning, greatness of years, devotion to the chosen profession, family traditions, and extraordinary responsibility for the actions of future generations. A dynasty is a continuous series of generations that pass on professional skills from family to family and the best family traditions. In the past, the dynasty was named after its ancestor or prominent representative. It is about such a noble dynasty of physicians. This is a world-famous family which ancestor is M. S. Bokarius, prominent scientist, forensic medical examiner, humanist and educator. It is no exaggeration to say that Mykola Mykolayovych founded not one dynasty, but two. The first is the scientific community of forensic medical examiners, people who from generation to generation worthily support the principles of scientific activity, laid down in 1925, when Hon. Prof. M. S. Bokarius Kharkiv Research Institute of Forensic Examinations was established. However, Mykola Serhiyovych left behind not only a huge scientific achievement and thousands of students and followers. Perhaps his most important legacy is the establishment of a family business, where each of the descendants measures their lives according to the strict criteria of the Bokarius dynasty. Mykola Mykolayovych Bokarius was the first of his family was an outstanding forensic expert, educator of a constellation of forensic medical examiners and criminalists. Kira Mykolaivna Bokarius, Mykola Mykolayovych granddaughter, continued the father’s work with dignity. The youngest son of M. S. Bokarius was Vitaliy Mykolayovych Bokarius, well known scientist, respected forensic medical examiner whose works are still popular among students and teachers. He passed on to his two sons, Leonid and Sergei, a desire for knowledge, respect for the profession and selfless service to the ideals of goodness and honor. Five generations of Bokarius medical dynasty still serve the people, giving sincerity of their souls, sensitivity of heart for the benefit of society. They all have something to be proud of, because they carefully preserve traditions, pass on from generation to generation experience, knowledge and skills, being a unique resource and human capital in the modern world, transmitting experience, knowledge and family values. Medicine is the profession of their destiny!